1998
DOI: 10.1074/jbc.273.21.13359
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor Induces Rapid Increases in Functional Cell Surface Low Density Lipoprotein Receptor-related Protein

Abstract: The low density lipoprotein receptor-related protein (LRP) is a large endocytic receptor that binds multiple ligands and is highly expressed in neurons. Several LRP ligands, including apolipoprotein E/lipoproteins and amyloid precursor protein, have been shown to participate either in Alzheimer's disease pathogenesis or pathology. However, factors that regulate LRP expression in neurons are unknown. In the current study, we analyzed the effects of nerve growth factor (NGF) treatment on LRP expression, distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 64 publications
2
47
0
Order By: Relevance
“…One study performed in isolated rat adipocytes has shown that NGF has an antilipolytic and lipogenic effect (45). Subsequently, an upregulation by NGF of LDL receptor-related protein has also been described in different cell types, including PC12 cells (46), which suggests a protective role of NGF in the atherosclerotic process.…”
Section: Discussionmentioning
confidence: 99%
“…One study performed in isolated rat adipocytes has shown that NGF has an antilipolytic and lipogenic effect (45). Subsequently, an upregulation by NGF of LDL receptor-related protein has also been described in different cell types, including PC12 cells (46), which suggests a protective role of NGF in the atherosclerotic process.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of apoE and phosphatidylcholine precursors increase in parallel with neurite sprouting in the lesioned hippocampus, probably enabling membrane synthesis and dendritic rearrangement (46). The importance of LRP-mediated endocytosis in the growth and maintenance of neuronal structural plasticity is underscored by the rapid mobilization of LRP to the plasma membrane from intracellular storage pools following treatment with nerve growth factor (47). Growth factor-induced increase in the endocytosis of lipoproteins may be a way of providing neurons with the lipids and proteins necessary for growth and regeneration.…”
Section: Trafficking Of Anionic Liposomes In Hippocampal Neumentioning
confidence: 99%
“…These experiments revealed that LRP can undergo phosphorylation in untransfected cultured cells under steady-state conditions, but they did not determine whether these phosphorylation events include tyro-sine residues. Phosphorylation of the LRP tail by serine/threonine kinases had previously been reported (26). To address this question and to determine whether the coprecipitated 60-kDa protein may also be phosphorylated on tyrosine residues, we immunoprecipitated LRP from J774 cells that had been treated (Fig.…”
Section: Rap Blocks P59mentioning
confidence: 99%